Betty Doll - Polacco, Patricia (New York : Philomel Books, 2001)
From the day the author's mother first sewed Betty Doll together stitch-by-stitch to the day, many years later, when she discovered she had cancer, her sweet Betty Doll was there--through blizzards, sickness, and weddings.
AD 540
Keywords: Barber, Mary Ellen, -- d. 1996.; Union City Region (Mich.) -- Biography; Polacco, Patricia -- Family; Dolls; Mother-daughter relationship; Women -- Biography